2017
DOI: 10.11596/asiajot.13.23
|View full text |Cite
|
Sign up to set email alerts
|

Influence of interaction among the elderly through amusement on their physiological function: One-month introduction at a day care service center for the elderly

Abstract: The 65-year-old or older population exceeded 30 million with rapid aging in Japan. It is predicted to peak with about 39 million in 2042 and the 75-year-old or older population will continuously increase thereafter. The Ministry of Health, Labour and Welfare promotes construction of the Integrated Community Care System targeting 2025 [1], and how to prevent a need-fornursing care state in the elderly is an urgent issue. Regarding the prevention of nursing care, improvement of sociality of the elderly, such as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 19 publications
(21 reference statements)
0
3
0
Order By: Relevance
“…Shimizu et al showed that smiling induced psychological changes, such as reductions in negative emotions and improvements in mood, and psychological changes contributed to reducing salivary amylase activity [39]. We previously suggested that an active response based on amylase activity was promoted by interactions through amusement in elderly day care services and subjects felt comfortable with communicating with others through amusement [19]. In the complex-type program employed in the present study, subjects participated in individual exercise programs and blackjack as an amusement program.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Shimizu et al showed that smiling induced psychological changes, such as reductions in negative emotions and improvements in mood, and psychological changes contributed to reducing salivary amylase activity [39]. We previously suggested that an active response based on amylase activity was promoted by interactions through amusement in elderly day care services and subjects felt comfortable with communicating with others through amusement [19]. In the complex-type program employed in the present study, subjects participated in individual exercise programs and blackjack as an amusement program.…”
Section: Discussionmentioning
confidence: 99%
“…In the complex-type program employed in the present study, subjects participated in individual exercise programs and blackjack as an amusement program. They may have gradually got close to each other by interactions through blackjack and formed new relationships with others, which may have been pleasant [19]. Therefore, salivary amylase levels slightly decreased, indicating that the amusement/exercise complex program was enjoyable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation